1999
DOI: 10.3168/jds.s0022-0302(99)75282-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fat Reduction on Chemical Composition, Proteolysis, Functionality, and Yield of Mozzarella Cheese

Abstract: Mozzarella cheese was made from skim milk standardized with cream (unhomogenized, 40% milk fat) to achieve four different target fat percentages in the cheese (ca. 5, 10, 15, and 25%). No statistically significant differences were detected for cheese manufacturing time, stretching time, concentration of salt in the moisture phase, pH, or calcium as a percentage of the protein in the cheese between treatments. As the fat percentage was reduced, there was an increase in the moisture and protein content of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
120
4
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(178 citation statements)
references
References 14 publications
50
120
4
4
Order By: Relevance
“…This trend was observed throughout cheese ripening and is in close agreement with other researchers (Katsiari and Voutsinas 1994;Rudan et al Sipahioglu et al 1999;Romeih et al 2002;Arslan et al 2010a). The higher salt content in the low-fat cheeses may be linked to their higher moisture contents (Romeih et al 2002;Kavas et al 2004).…”
Section: Composition Of Cheesesupporting
confidence: 93%
See 2 more Smart Citations
“…This trend was observed throughout cheese ripening and is in close agreement with other researchers (Katsiari and Voutsinas 1994;Rudan et al Sipahioglu et al 1999;Romeih et al 2002;Arslan et al 2010a). The higher salt content in the low-fat cheeses may be linked to their higher moisture contents (Romeih et al 2002;Kavas et al 2004).…”
Section: Composition Of Cheesesupporting
confidence: 93%
“…Banks et al (1994) found that as fat content of Cheddar cheese decreased, moisture content increased. Similar results were reported by Rudan et al (1999) for Mozzarella cheese and Kumar et al (2011) for Indian cheese (paneer).…”
Section: Composition Of Cheesesupporting
confidence: 88%
See 1 more Smart Citation
“…Theoretical yield was calculated using Van Slyke and Price formula as modified by Barbano (Rudan et al 1999). Fat and protein recoveries were calculated from the weight (yield) of each product multiplied by its percentage of fat/protein/total solids content and then divided by the total weight/percentage of fat/protein/total solids present in the original milk and multiplied by 100.…”
Section: Methodsmentioning
confidence: 99%
“…For example, when fat content was reduced to below 15% proteolysis during storage decreased and the hardness of cheese increased, which in turn also adversely affected its functionality (Rudan et al, 1999).…”
Section: Flavormentioning
confidence: 99%